Screening and optimization of biosurfactant producing bacteria from oil mill area MIDC, Parbhani (M.S.) - Gujar, R S; Hamde, V S (Journal of Ecobiotechnology, 2012)
Biosurfactant are amphiphilic compounds produced on living surfaces, mostly on microbial cell surfaces. They are biodegradable non- toxic and ecofreindly materials. Pseudomonas aeruginosa isolated from oil mill area produced biosurfactant at 370C at pH 7 on YPG medium and mineral salt medium. The biosurfactant production depends on the fermentation conditions, environmental factors and nutrient availability. The extraction of the biosurfactant from the cell free supernatant using the solvent extraction procedure & the qualitative and quantitative analysis has been discussed with appropriates equipment details.